(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The school of acting skills became a powerful and fundamental factor in the influence of the theater on pop art.The actor plays the main role in the variety show. Armed with the expressive tools typical of dramatic theater, he attracts the attention of the audience, often without stage decoration, lighting, make-up, props, tricks, or using all of them to a small extent, he becomes a number, a main participant in the performance.Variety acting skills are the foundation upon which the entire concept of the role rests. Pop artist, his inner life should be based on stage in any genre. Otherwise, the pop number will consist of pure tricks, a collection of stereotyped gags, useless anecdotes, and crudely interpreted reprises. All this turns into nonsense, meaningless talk.